The Influence of Organizational Agility to Growth Business with Organizational Health as Variables Moderation at PT Syntax Corporation Indonesia - Ginna Novarianti Dwi Putri Pramesti (Ravine Publisher, 2026)
This study aims to analyze the influence of organizational agility on business growth and to examine the moderating role of organizational health in that relationship at PT Syntax Corporation Indonesia, a digital talent development company operating in Indonesia's rapidly evolving knowledge economy. Using a quantitative associative approach, data were collected through questionnaires distributed to 85 respondents consisting of managers and operational staff and analyzed using Moderated Regression Analysis (MRA). The findings reveal that organizational agility has a positive and significant effect on business growth (?=0.487; p=0.000), and that organizational health significantly moderates this relationship (?=0.218; p=0.031; ?R²=0.159), strengthening the impact of agility on business growth. These results imply that organizations must simultaneously invest in both agility capabilities and organizational health as integrated strategic priorities, rather than treating them as separate management agendas. This study contributes to the literature by providing the first empirical evidence of organizational health as a positive moderator of the agility–business growth relationship within Indonesia's digital talent development sector, extending contingency theory to knowledge-based organizational contexts.